An Ultra-Stable Polysaccharide Gel Plugging Agent for Water Shutoff in Mature Oil Reservoirs - Yang Yang; Shuangxiang Ye; Ping Liu; Youqi Wang (Applied Sciences)
Polyacrylamide-based gel plugging agents are extensively utilized in oilfields for water shutoff. However, their thermal stability, salt tolerance, and shear resistance are limited, making it difficult to achieve high-strength plugging and maintain stability under high-temperature and high-salinity reservoir conditions. This study proposes the use of chitosan (CTSs), a polysaccharide with a rigid cyclic structure, as the polymer. The organic cross-linker N,N′-methylenebisacrylamide (MBA) is incorporated via the Michael addition reaction mechanism to develop an ultra-stable, organically cross-linked chitosan gel system. The CTS/MBA gel system was evaluated under various environmental conditions using rheological testing and thermal aging to assess gel strength and stability. The results demonstrate significant improvements in gel strength and stability at high temperatures (up to 120 °C) and under high-shear conditions, as the increased cross-linking density enhanced resistance to thermal and mechanical degradation. Rapid gelation was observed with increasing MBA concentration, while pH and salinity further modulated gel properties. Scanning electron microscopy revealed the formation of a three-dimensional microstructure after gelation, which contributed to the enhanced properties. This study provides novel insights into optimizing polymer gel performance for the petroleum industry, particularly in high-temperature and high-shear environments.